Tanggung Jawab Penjamin dalam Penanguhan atau Pengalihan Penahanan Tersangka atau Terdakwa - Wirawan, Vian Nando; Suyatna (Indonesian Journal of Law and Justice, 2024)
The provisions of Article 1 point 21 of the Criminal Procedure Code state that detention is the placement of a suspect/defendant in a certain place by an investigator, public prosecutor or judge with his or her determination and in a regulated manner. in this law. Detention is the placement of a suspect/defendant in a certain place by an investigator, public prosecutor, or judge with his or her determination, with the conditions and methods regulated in this law. Therefore, detention is a form of deprivation of a person's freedom of movement and is a threat aimed at giving a feeling of regret to someone who has committed an offense. Detained suspects/defendants have several rights, one of which is the right to submit a request for suspension or the right to transfer detention. According to the provisions of Article 31 of the Criminal Procedure Code, a suspension of detention can be granted by investigators, public prosecutors or judges in accordance with their respective authorities with or without cash collateral or personal guarantees, based on predetermined conditions. The purpose of this research is to determine the responsibility of the guarantor if a suspect or accused who is detained or transferred to detention escapes. The research method uses normative juridical with a statutory and conceptual approach. The result of this research is that a suspension of detention can be granted by the police investigator as the detention institution, if the suspect/accused or guarantor has fulfilled the conditions that have been set. However, during the suspension of detention, the suspect/defendant escapes and is not found within a period of 3 (three) months, then (the guarantor) is responsible for bearing all risks and consequences that arise, namely by depositing the security deposit. in the amount specified in the agreement at the beginning. granting suspension of detention